REVITALISASI LEGENDA BATU HODA MELALUI NASKAH DRAMA - Donganta Donganta; Febri Yanti Arfansyah Harapan; Sartika Sari (elt, 2021)
ABSTRACT The legend of Batu Hoda is a folk tale from the Simanindo sub-district, Samosir district, which tells of a mare who is waiting for her lover a stallion to meet on the shores of Lake Toba. The form of the story about the origin of Batu Hoda is not yet known by many people, this is due to the lack of innovation in telling stories to the community, especially children. Therefore, people have lost interest in telling or curiosity about legends. The research method used is a qualitative approach with the aim of finding information about the story of Batu Hoda. As the main design, such as interviews with several informants or the surrounding community. The results of this study were formulated in the form of re-searching the legend of Batu Hoda in the form of presenting the story that was played. The selection of drama script media as media is expected to be one of the efforts to preserve folklore. The drama script provides a retelling style with dasi and illustrations and makes it easier for people to get carried away in the Batu Hoda story. Keywords: Simanindo's glasses, Folklore, Drama Script, Batu Hoda